Safety of Phacoemulsification with Gradual Hydro Dissection on Posterior Polar Cataract - Parmono, Ahda Firstaputra; Pardianto, Gede; Purworini, Diyah (Universitas Airlangga, 2024)
Introduction: Phacoemulsification has been a procedure of choice for treating cataractous lenses and restoring visual function. Posterior polar cataract have been one of many cases in which phaco surgeons should be careful and aware for more to perform phacoemulsification. One hydrodissection procedure is safe to perform as an alternative to hydrodileniation during phacoemulsification for posterior cataract. It is called gradual hydrodissection. Methods: This study performed a quasi-experimental pre-post study that tested the safety of gradual hydrodissection in phacoemulsification in 50 eyes of 50 patients. The safety parameter used in this study includes the incidence of posterior capsule rupture and nucleus drop during phacoemulsification until surgery is finished. Descriptive statistics were used to summarize the characteristics of the study participants, such as age, sex, race, eye laterality, and previous intraocular surgery. A paired student’s t-test was conducted to compare preoperative and postoperative values for visual acuity and intraocular pressure. The P <0.05 was considered the level of statistical significance. Results: There was no complication of the posterior capsule during the hydrodissection procedure. There was a statistically significant difference in visual acuity and intraocular pressure before and after surgery by P value <0.001. All of the phacoemulsification studies were considered uneventful and successful. Conclusions: Gradual hydrodissection may be safe to be performed in phacoemulsification for posterior polar cataract.